2016
DOI: 10.2197/ipsjjip.24.339
|View full text |Cite
|
Sign up to set email alerts
|

Magnet or Sticky? Measuring Project Characteristics from the Perspective of Developer Attraction and Retention

Abstract: Open Source Software (OSS) is vital to both end users and enterprises. As OSS systems are becoming a type of infrastructure, long-term OSS projects are desired. For the survival of OSS projects, the projects need to not only retain existing developers, but also attract new developers to grow. To better understand how projects retain and attract contributors, our preliminary study aimed to measure the personnel attraction and retention of OSS projects using a pair of population migration metrics, called Magnet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…For example, we believe we can further strengthen the follow-up network analysis conducted by Yu et al [26]. Yamashita et al [27], [28] classified OSS projects by using metrics of magnet and sticky and identified what projects retain and attract contributors. By matching the information of our framework with these metrics, we may be able to analyze the behavior of contributors in more detail.…”
Section: Discussionmentioning
confidence: 68%
“…For example, we believe we can further strengthen the follow-up network analysis conducted by Yu et al [26]. Yamashita et al [27], [28] classified OSS projects by using metrics of magnet and sticky and identified what projects retain and attract contributors. By matching the information of our framework with these metrics, we may be able to analyze the behavior of contributors in more detail.…”
Section: Discussionmentioning
confidence: 68%
“…But Dabbish et al 31 and Yamashita et al 32 observed in their research a positive impact on the team as it may bring fresh ideas and knowledge to them, and also some respondents in the survey conducted in 2019 by/termed it good when oldies dropout as they are resistant to change. Iaffaldano et al 24 urge to find a balance between developer turnover and retention.…”
Section: Related Workmentioning
confidence: 92%
“…The higher the number of contributors to a package repository shows that the package is more likely to attract developers [59].…”
Section: Contributorsmentioning
confidence: 99%